2021
DOI: 10.1097/cej.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in moderately/poorly differentiated breast cancer types

Abstract: Background Diagnostic delay of breast cancer related to the false-negative assessment of the healthcare provider leads to tumor progression and might worsen the outcome. Previous studies found some factors associated with provider-related diagnostic delay; however, tumor biology has tended not to be considered. The aim of our study was to find differences in diagnostic delay of poorly differentiated breast cancer types.Methods Data of 970 patients with newly diagnosed moderately/poorly differentiated (G2/3) br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The upper exterior quadrant was the most afflicted in 58% of patients in our study. clinically detectable tumor than at the stage of a mammographic finding with a high false-negative rate during complementary examinations, thus increasing the time to diagnosis [14]. In our series, the delay was longer than 3 months in 80% of instances, which is consistent with the findings of another study, which found a delay of more than 3 months in 57% of cases [15].…”
Section: Triple-negative Breast Cancer Is Distinguished By No Estroge...supporting
confidence: 91%
“…The upper exterior quadrant was the most afflicted in 58% of patients in our study. clinically detectable tumor than at the stage of a mammographic finding with a high false-negative rate during complementary examinations, thus increasing the time to diagnosis [14]. In our series, the delay was longer than 3 months in 80% of instances, which is consistent with the findings of another study, which found a delay of more than 3 months in 57% of cases [15].…”
Section: Triple-negative Breast Cancer Is Distinguished By No Estroge...supporting
confidence: 91%
“…The TNBC phenotype appears with an aggressive pattern [13] and to be closely associated with a hereditary cause of the disease [14], most frequently the Hereditary Breast and Ovarian Cancer (HBOC) syndrome. HBOC is an autosomal dominant condition caused by germline mutations in BRCA1 and BRCA2 genes.…”
Section: Introductionmentioning
confidence: 99%
“…MpBC is rarely seen in general radiology practice, even in BC referral centers (Shin et al ., 2007; Elfgen et al ., 2022). Although there are few studies describing the main diagnostic imaging findings of MpBC, it usually shows a mass with an oval/round shape and indistinct margins (Park et al ., 2000; Günhan-Bilgen et al ., 2002; Yang et al ., 2007; Choi and Shu, 2012; Leddy et al ., 2012; Langlands et al ., 2016; Kim et al ., 2018; Alhaidary et al ., 2022).…”
Section: Breast Imagingmentioning
confidence: 99%